Histological Studies on Digestive System Development and Early Feeding Activity of Pangasius Hybrid Larvae - Agus Putra AS; M. Fauzan Isma; Rindhira Humairani; Yusrizal Akmal (Journal of Aquaculture and Fish Health, 2020)
AbstractThis study was conducted to investigate the digestive system development and early feeding activity of Pangasius hybrid larvae. Four crossbreeding program in triplicate were examined between Pangasius hypopthalmus and Pangasius nasutus. Results showed that the digestive systems of both hybrid larvae were poorly developed immediately after hatching. The digestive system of the newly hatched larvae consisted of straight undifferentiated tube and anus still closed. The gastro intestinal tract, liver and pancreas were formed and developed by 2-dAH. The zymogen granules were also observed in the pancreas and thus imply that function of pancreas started before the exogenous feeding period. Gastric glands were only present and started to secrete enzyme on 6-dAH. Artemia were first seen in digestive tract of the larvae at 54-hAH. However, onset of exogenous feeding was detected at 60-hAH, whereas stomach became enlarged with isometric epithelium cells, which were different from the elongated cells in the intestinal part. Keywords: Pangasius, hybrid, digestive system, histology